2020
DOI: 10.1016/j.chempr.2020.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of PdII and PtII Supramolecular Copolymer with Sequential Multiblock and Amplified Phosphorescence

Abstract: Supramolecular copolymers constitute a fundamental new class of functional materials attracting burgeoning interest, but examples that display phosphorescence and long-lived excited states are rare. Herein, we describe the synthesis of sequential phosphorescent multi-block supramolecular copolymers in one and multiple dimensions using pincer Pt II and Pd II complexes as building blocks by manipulating out-of-equilibrium self-assemblies via the living supramolecular polymerization approach. Doping a small amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 71 publications
3
95
0
7
Order By: Relevance
“…Other examples of molecular amphiphiles that undergo living supramolecular polymerization include amphiphilic square planar Pt(II) phenanthroline and related complexes, [225][226][227][228][229] perylene bisimides, 221,230 and a wide range of additional π-stacking and hydrogen-bonding species. 210,231,232 Complex architectures, such as well-defined supramolecular block copolymers, have also been successfully prepared and their study represents an exciting new area within the flourishing field of supramolecular polymers.…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Other examples of molecular amphiphiles that undergo living supramolecular polymerization include amphiphilic square planar Pt(II) phenanthroline and related complexes, [225][226][227][228][229] perylene bisimides, 221,230 and a wide range of additional π-stacking and hydrogen-bonding species. 210,231,232 Complex architectures, such as well-defined supramolecular block copolymers, have also been successfully prepared and their study represents an exciting new area within the flourishing field of supramolecular polymers.…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 99%
“…210,231,232 Complex architectures, such as well-defined supramolecular block copolymers, have also been successfully prepared and their study represents an exciting new area within the flourishing field of supramolecular polymers. 221,222,229,233,234 For example, A-B-A supramolecular block copolymers of amphiphilic perylene bisimides have been fabricated by seeded living polymerization (see Figure 5c). 221 Cooperative supramolecular block copolymerization has been achieved based on naphthalene diimide monomers with optically distinct green and red fluorescence (see Figure 5d).…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 99%
“…While there has been remarkable progress recently with preparing supramolecular block copolymers under thermodynamic control [60][61][62] or by slow cooling of monomer mixtures [63][64][65] , a growing number of such precision polymers has been prepared by LSP, which can provide superior structural and sequence control. However to date, these LSP approaches either rely on the modification of the polymerizable core, e.g., substituents are attached to the core of rylene dyes 16,66 or the complexation of different metal ions to identical ligands 67,68 . A modular approach based on the variation of the side chain, as pioneered by Otto, Faul, Manners and Sugiyasu 19,32,69 , would be complementary to these methods and could offer distinct advantages for applications in organic materials science.…”
Section: Monomersmentioning
confidence: 99%
“…Complex supramolecular polymerization behaviour of 1 Self-assembled structures of d 8 metal complexes exhibit particularly interesting photophysical properties [29][30][31][32][33] and the presence of the metal fragment oen enables multiple competing non-covalent interactions, which is benecial to create kinetic aggregates. [34][35][36][37] Preliminary self-assembly studies of the (S)-enantiomer of Pd complex 1, however, suggested the presence of a single supramolecular species if monomer solutions in methylcyclohexane (MCH) were cooled from 363 K to 283 K at a rate of 1 K min À1 .…”
Section: Resultsmentioning
confidence: 99%